Claws that catch eaudiobook Looking glass series, book 4. - Ringo, John (Looking Glass, 2010)
The Galaxy at Risk! Humans have come a long ways since the looking glass gates first appeared and an alien menace turned a motley crew of scientists, sailors and force recon Marines into battle-hardened space adventurers. Now with other species running scared, it's up to humans to take the lead and mold a weapon capable of checking the Dreen—a galactic cancer that has so far proved unstoppable. Their arsenal is a hodge-podge of powerful technologies begged, borrowed and/or looted from across the galaxy and cobbled together on what has to be the strangest ship ever to ply the starways: the good ship Vorpal Blade II! Great Ideas! Cool Space Ships! Evil Alien Butt Blasted to Smithereens!